Severe osteogenesis imperfecta: case report - Bastos,Fernando (2010)
ABSTRACT The authors present a case of Osteogenesis Imperfecta, emphasizing the clinical and epidemiological characteristics, forms of classification and treatment of the disease. This is an important case not only to the knowledge of pediatricians and orthopedists, but also for other professionals involved with the problem. This article has been jointly described by the Departments of Pediatrics and Neonatology of the Girassol Clinic in Luanda Capital of the Republic of Angola, Africa.